WRITTEN CORRECTIVE FEEDBACK GIVEN BY TEACHERS OF MTSN DURIAN TARUNG PADANG ON STUDENTS’ GRAMMATICAL ERRORS - Rahmi Roza P; Saunir Saun; Fitrawati Fitrawati (Journal of English Language Teaching, 2016)
This research aimed at finding out the types of written corrective feedback used by English  teachers of a junior high school on student’s grammatical errors , and problems related to written corrective feedback on grammatical errors from the teacher’s perspectives. This is a descriptive research in which the population was all of English teacher of MTsN Durian Tarung Padang. By using maximal variation sampling technique, all of the teachers, who were five teachers, were chosen to be the sample. The first instrument used was documents which were notebooks and exercise books of the students of the school in the year 2015/2016, and the second instrument was interview with the teachers. From the research, it was found that only three types of the five types were practiced by the teachers. They were, consecutively written from the most frequently used to the least, direct corrective feedback, indirect corrective feedback and metalinguistic feedback with the use of error codes. In addition, problems related to written CF were repetition of errors, students proficiency, student’s attitude, time-consuming, ineffectiveness of existing error feedback practice, and readability of students writing. Therefore, English teacher, future teachers should enrich their knowledge of written corrective feedback, optimizing their correction to optimize the benefits to the students language development and find solution to solve problem related to written corrective on students’ grammatical error.